TIPOLOGI MIGRASI: SUATU ALTERNATIF PENGEMBANGAN KONSEP - Sukamdi Sukamdi (Populasi, 1991)
Using the migration survey done by Population Studies Center Gadjah Mada University, this article tries to find out the possibility in improving the definition of migration. It is based on the idea that migrationis a process. It means that migration can be defined more than dichotomy of the concept of permanent and sirculation. The reason is that the dichotomy tends to ignore the possibility of migrants occupying one or more categories intermediate to the two polar types. By introducing the variable of intention to remain at the destination and the length of migrants stay in the destination, a four fold typology of migrant type can be created: circular migrants, migrants who intend to remain circular, migrants who intend to be permanent and permanent migrants.